METAMIZOLE VERSUS KETOROLAK OF POSTOPERATIVE CLOSED FRACTURE PAIN MANAGEMENT AT dr. ISKAK TULUNGAGUNG HOSPITAL : A COST EFFECTIVENESS ANALYSIS - Prasetyo, Eko Yudha; Kusumaratni, Dyah Ayu; Aditya Ayuning Siwi, Mayang (Journal Medicine And Clinical Pharmacy, 2025)
The pain that appears in postoperative patients is acute pain, but pain that is not properly managed will develop into chronic pain and have long-term negative effects  and also have financial impacts. Metamizole is commonly used in pain management, while ketorolac is currently positioned as an alternative option. The availability of various analgesic options must be accompanied by comparative data on effectiveness and cost assessment.This aim to compare the cost–effectiveness of two therapies for moderate and severe acute pain, Metamizole (3x1g) and Ketorolac (3x30mg) for closed fracture postoperative pain management.. This study is descriptive comparative research using a cross sectional design with retrospective data collection. The sample in this study was the medical records and financial records of BPJS class III closed fracture surgery patients. Cost estimation measured from the provider's perspective. The types of costs considered are all costs directly related to health care at the hospital. Costs are measured in Indonesian rupiah (IDR) currency units. This research is short-term research so the researcher did not analyze the discount rate(0%). The findings of this study showed that Metamizole is a drug with higher effectiveness (37.93%) than ketorolac (35.48%), with a total direct medical cost of metamizole of IDR. 21,990,051 and ketorolac IDR. 23,041,427. ACER value of metamizole IDR. 579,754 and ketorolac IDR. 649,420. Based on the calculation of these real numbers, Metamizole is more cost effective than ketorolac in postoperative fracture pain management. However, statistically the effectiveness and cost of the two therapies did not have a significant difference.